Analisis Sistem Pelayanan Rawat Jalan di Rumah Sakit Umum Daerah Koja - Dinda Fitriyani; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2023)
This research uses qualitative research methods with a case study approach, observation, interviews, and data collection which aims to answer questions about how the outpatient service system at Koja Hospital. This qualitative research is based on primary and secondary data. Primary data in this study was obtained by conducting observations, interviews, and documentation, while secondary data was obtained through books, previous research, and articles related to the research. The outpatient service system at Koja Hospital still has obstacles in the system, including data entry constrained by signals because it uses a computerized system, the system has an error, sometimes the patient has been called by the nurse several times to be examined but the patient is not in place. From the results of this study, Koja Regional General Hospital already has an adequate system by using an online system, namely SIDOLAN, with this system it will make it easier for patients to seek outpatient treatment according to the intended polyclinic and the intended specialist.